Exopolyphosphatase of Pseudomonas aeruginosa is essential for the production of virulence factors, and its expression is controlled by NtrC and PhoB acting at two interspaced promoters - Gallarato, Lucas Antonio (2014)
The exopolyphosphatase (Ppx) of Pseudomonas aeruginosa is encoded by the PA5241 gene (ppx). Ppx catalyses the hydrolysis of inorganic polyphosphates to orthophosphate (Pi). In the present work, we identified and characterized the promoter region of ppx and its regulation under environmental stress conditions. The role of Ppx in the production of several virulence factors was demonstrated through studies performed on a ppx null mutant. We found that ppx is under the control of two interspaced promoters, dually regulated by nitrogen and phosphate limitation. Under nitrogen-limiting conditions, its expression was controlled from a σ54-dependent promoter activated by the response regulator NtrC. However, under Pi limitation, the expression was controlled from a σ70 promoter, activated by PhoB. Results obtained from the ppx null mutant demonstrated that Ppx is involved in the production of virulence factors associated with both acute infection (e.g. motility-promoting factors, blue/green pigment production, C6–C12 quorum-sensing homoserine lactones) and chronic infection (e.g. rhamnolipids, biofilm formation). Molecular and physiological approaches used in this study indicated that P. aeruginosa maintains consistently proper levels of Ppx regardless of environmental conditions. The precise control of ppx expression appeared to be essential for the survival of P. aeruginosa and the occurrence of either acute or chronic infection in the host.